Endosurgical Remodeling of Wide-Necked Bifurcation Aneurysms - Dayawansa, Samantha; Sulhan, Suraj; Huang, Jason H.; Noonan, Patrick T. (Frontiers in Neurology, 2019)
Background: Wide-necked cerebral aneurysms at a bifurcation can be difficult to treat with endovascular techniques despite recent advancements. Objective: We describe a new technique of micro-scaffold remodeling of the aneurysm neck of wide-necked bifurcation aneurysms by placing one or more microcatheters and/or wires in the efferent vessels. We hypothesize that this technique would be a better choice to change the branch angulation, allowing for an improved configuration to stably deploy coils. We present a retrospective case series to illustrate this technique. Methods: 17 wide-necked bifurcation aneurysms in 17 patients were coil embolized using this technique during a 3 year study period. Branch-vessel microcatheters and/or microwires were used to remodel the aneurysm neck and support the coil mass. Statistical analysis of the branch angulation and neck-width changes were performed during treatment. Long-term clinical outcome and follow-up angiography was obtained in 8 patients. Results: Eleven patients had complete occlusion of their aneurysm (Raymond-Roy Class I), and 6 patients had Raymond-Roy Class 2 immediately after treatment. Efferent vessels demonstrated a statistically significant change in angulation with insertion of microcatheters or microwires, while neck width did not change significantly. There were four intraoperative complications and no neurological morbidity in the immediate post-operative period. Complete occlusion was documented for all 10 subjects with long-term follow-up. Conclusions: The micro-scaffold endosurgical remodeling technique is a useful adjunct in treating wide-necked bifurcation aneurysms. By elevating branch vessels away from the aneurysm neck, this technique allows for dense coil packing while decreasing the need for balloon or stent assistance.